Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1021/jp982816g
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Reversal in AlPO4-5 Crystals Containing Polar or Nonpolar Organic Molecules:  A Scanning Pyroelectric Microscopy Study

Abstract: Large AlPO 4 -5 crystals containing different polar or nonpolar guest molecules have been studied with scanning pyroelectric microscopy. Calcined crystals are pyroelectric with a polar structure that reverses in polarity at the center of the crystal. Consequently all these crystals are twinned. The temperature dependence of the pyroelectric coefficient reveals a genuine pyroelectric crystal structure, which spontaneous polarization decreases from 30 µC/m 2 to almost zero at a Curie temperature, T c , of 50°C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Klap et al have shown in a series of papers [24][25][26] that the Al À O À P vector (of the T À O À T bonds parallel to c) always points in the same direction (in fact, AFI crystal growth only takes place in that direction), thus giving a permanent polarisation to the crystal along the c direction. This macroscopic polarisation may cause the alignment of the water molecules in the 6-MR channels.…”
Section: Resultsmentioning
confidence: 99%
“…Klap et al have shown in a series of papers [24][25][26] that the Al À O À P vector (of the T À O À T bonds parallel to c) always points in the same direction (in fact, AFI crystal growth only takes place in that direction), thus giving a permanent polarisation to the crystal along the c direction. This macroscopic polarisation may cause the alignment of the water molecules in the 6-MR channels.…”
Section: Resultsmentioning
confidence: 99%
“…12 In the present paper we want to address the relaxational behavior of AlPO 4 -5/pNA by dielectric spectroscopy. …”
Section: Introductionmentioning
confidence: 89%
“…This host-guest system is of particular interest since the highly polar ͑and hyperpolarizable͒ pNA molecules will be adsorbed in a preferred direction, leading to a macroscopic polarization which gives rise to a secondharmonic generation activity 10 and to pyroelectricity. 11,12 Owing to the small channel diameter of 0.73 nm, the pNA molecules can neither pass each other nor flip around their short molecular axis. Infrared measurements revealed a high molecular orientation with a mean deviation angle of the long molecular axis from the channel direction of less than 15°at 273 K. 13 Another important feature of the aligned pNA molecules is their ability to form single or even double hydrogen bonds, the probability of which is temperature dependent.…”
Section: Introductionmentioning
confidence: 99%
“…AFI crystals contain aluminum-oxygen-phosphorus pairs pointing in the same direction along the crystal axis, forming a macroscopically preferred direction. 10 Hence, an excess of one type of enantiomers may be achieved during the growth process of chiral CNTs because of this asymmetry. Indeed, molecular mechanics computations 11 demonstrate that for some organic molecules, one helical arrangement is more stable than the other in the channel of AFI crystal, and this can lead to a longrange chirality in the whole solid.…”
Section: ͑3͒mentioning
confidence: 99%